Temporal analysis of the use of birds, as environmental sentinels in the monitoring of contamination by pesticides (Research, Society and Development, 2020)
Upon arrival of market globalization, a new economic model called agribusiness emerged, which is based on global political representation, through the interests of multinational business conglomerates. As a consequence, new agricultural production methodologies have emerged, where ecological destructuring of the environment is common, caused by the disordered use of pesticides. The exposure of non-target organisms to these chemical compounds is quite common, resulting in numerous cases of acute poisoning in the wild population, particularly in birds, which have low levels of detoxifying enzymes, increasing their sensitivity. The objective of the work was to conduct a research, through the scientometric approach, to verify and characterize the development of the world scientific knowledge, on the contamination of insectivorous birds by pesticides used in agriculture over 21 years. 16 studies were found, distributed in nine countries that studied 50 species of birds framed in four categories of population status. The results showed that they had at least one organ / tissue / structure (liver, feces, stomach bolus, blood plasma, muscle tissue, food items, eggs) contaminated by one of the 21 types of chemical compounds found in the analyzed articles. Although the existence of a global theoretical gap has been verified in relation to ecotoxicological research, demonstrating the impact of pesticides on the environment, in the studies analyzed in insectivorous birds, they proved to be excellent sentinels for environmental monitoring in the face of changes that occur in ecosystems, resulting agricultural production, and which can directly affect species of fauna and flora.